1993
DOI: 10.1177/027112149301300307
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Appropriate Strategies for Promoting Full Participation in Early Childhood Settings

Abstract: Integrating young children with disabilities into mainstream preschools with nondisabled children presents numerous challenges. One major stumbling block to integration is the seeming incompatibility of traditional didactic early intervention techniques with the developmentally appropriate practices common to quality mainstream preschool settings. We present strategies for intervention that are in harmony with developmentally appropriate practice and incorporate special educational principles that have enabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Research examining inclusive preschool settings has identified that while children with disabilities are included in play interactions, these exchanges are not as frequent for children with disabilities, compared with their typically developing counterpart (Odom et al, 2006). While research articulating possible inclusion strategies for childcare centers is available (Cavallaro, Haney, & Cabello, 1993;Diamond & Haung, 2005;Hanline, 1999;Sheldon, 1996), no researchers have undertaken a comprehensive review of literature examining appropriate inclusion strategies for children with physical disabilities in the preschool setting.…”
mentioning
confidence: 99%
“…Research examining inclusive preschool settings has identified that while children with disabilities are included in play interactions, these exchanges are not as frequent for children with disabilities, compared with their typically developing counterpart (Odom et al, 2006). While research articulating possible inclusion strategies for childcare centers is available (Cavallaro, Haney, & Cabello, 1993;Diamond & Haung, 2005;Hanline, 1999;Sheldon, 1996), no researchers have undertaken a comprehensive review of literature examining appropriate inclusion strategies for children with physical disabilities in the preschool setting.…”
mentioning
confidence: 99%
“…A the field of early childhood special education and early childhood education grow ever closer, a number of individuals have identified specific instructional strategies that both are effective for addressing the needs of young children with disabilities and appear to be acceptable within the DAP guidelines (Atwater, Carta, Schwartz, & McConnell, 1994;Cavallaro, Haney, & Cabello, 1993;Wolery & Fleming, 1993). These practices are presented here not as the absolute answer for determining developmentally appropriate procedures for children with disabilities (because all procedures must be scrutinized for their individual appropriateness) but because they are illustrations of approaches on which members of both fields can agree and because they are approache that can act as starting points for further collaborative program development.…”
Section: Instructional Procedures That "Bridge the Gap"mentioning
confidence: 99%
“…Adult direction was defined as an adult (not a child) leading and directing the activity. This high proportion of adult direction, as with the "mediocre" subscale scores on the ITERS, raises questions about the developmental appropriateness of these settings (Bredekamp &c Rosegrant, 1992;Cavallaro, Haney, &c Cabello, 1993), a finding that should be explored further in relation to child outcomes.…”
Section: The Cost Quality and Child Outcomes In Child Care Centers Smentioning
confidence: 99%